Preferensi Petani Terhadap Varietas Unggul Benih Padi di Kecamatan Sinjai Tengah Kabupaten Sinjai - Ansar Parawansa; Nurdin Nurdin; Sri Mardiyati; Syarifuddin Syarifuddin; Muh Arifin Fattah (Universitas Galuh, 2026)
Rice farming in Indonesia is strategic in addressing national food security, especially in rural areas such as Saohiring Village, Sinjai Tengah District, Sinjai Regency. The selection of superior varieties continues to be an important factor in increasing productivity, farm efficiency, and productivity. The purpose of this study was to analyze farmer preferences for superior varieties based on technical, social, and institutional characteristics. This study used a quantitative approach with a survey method on 100 randomly collected rice paddies. Data were analyzed using the Friedman test with a two-point Likert scale to understand differences in farmer preferences regarding quality, brand, and productivity attributes, pest and disease resistance, harvest age, and the role of agricultural extension workers. The results of the analysis show that farmer preferences differ depending on the attributes. Seed quality attributes still have the highest average ranking, indicating the highest preference, followed by pest and disease resistance and the role of extension workers having a high average. Then, productivity, harvest age, and seed brand have the lowest average ranking, which increases the lowest preference. In contrast to institutional factors in determining superior varieties, this test shows that farmers pay more attention to technical aspects and actual performance. The findings of this study indicate that farmer preferences in the study area are dominated by technological advancements, which hinders the development of empirically based decisions. It is hoped that these findings will form the basis for the development and dissemination of superior rice varieties that are more suited to local agroecosystem conditions and promote sustainable agriculture.